Calculation of proper bonus of liquid oseilation in not totally filled tanks (longitudiwal oscilation) - Синеглазов, В. М.; Кеменяш, Ю. М. (Proceedings of National Aviation University (archive), 2003)
Considered is the method of solution of problems of liqued oscielation by appllying the systems of garmonical functions. Me Hamilton-Ostrogradsky principale was used as the basic one. Calculation is adapted to concrete forms of tanks